EFL Learners’ Foreign Language Learning Anxiety and Language Performance: A Meta-Analysis Study - Dikmen, Melih (Muhammed ZİNCİRLİ, 2021)
The relationship between foreign language anxiety (FLA) and English as a foreign language (EFL) learners’ performance is constantly being examined through experimental and theoretical studies. The aim of this study is to examine the association between FLA and EFL performance through meta-analysis. As a result of an extensive literature review, 69 studies from fourteen countries (N= 23.150) were identified as eligible to be included in the analysis process. The overall correlation between FLA and EFL performance was calculated as -.61. In terms of moderator variables, the results revealed that while grade level and country in which studies were conducted did not have an effect on the association between FLA and EFL performance, type of anxiety was found to have a moderator effect. It was observed that listening, test, speaking, reading, and writing anxiety affected EFL learning performance respectively from the most to the least. Finally, publication year and sample size were found to have a significant effect on the association between FLA and EFL performance through meta-regression analysis. Based on the findings, it is concluded that in order to increase EFL learners’ performances, their foreign language anxiety should be decreased.